Fractional Flow Reserve Assessment of a Significant Coronary Stenosis Masked by a Downstream Serial Lesion - Lawrence Yu-Min Liu; Hsu-Ping Wu; Po-Lin Lin (Case Reports in Cardiology)
Fractional flow reserve (FFR) has been recognized as an effective tool to determine functional significance in intermediate coronary lesions and FFR-guided percutaneous coronary intervention (PCI) improves clinical outcomes. However, hemodynamic interaction between serial stenoses within one coronary artery complicates the assessment of functional severity of each individual lesion. We present a case in which FFR measurement by intracoronary bolus injection of adenosine helps to make appropriate revascularization decision in serial stenoses when the procedures are performed systemically and properly.